Are Muslim women less susceptible to oncogenic human papillomavirus infection? A study from rural eastern India. Issue 2 (1st February 2004) - Duttagupta, C.; Sengupta, S.; Roy, M.; Sengupta, D.; Bhattacharya, P.; Laikangbam, P.; Roy, S.; Ghosh, S.; Das, R.
Abstract : Muslim women are known to have lower incidences of cervical cancer and/or human papillomavirus (HPV) infection. Here we aim to determine any association that may be present between the oncogenic HPV16/18 infections and abnormal cytological lesions along with demographic and other attributes among Indian Muslim women ( n = 478) and compare with the neighboring Hindus ( n = 534) from a prospective cohort study. Agewise distribution of both subject-groups is similar. HPV16/18 infection is present in 9.6% Muslims and 7.5% Hindu women. Jointly atypical cells of undetermined significance (a typical cells of undetermined significance) and HPV16/18 are present in seven Muslim and two Hindu women. No high squamous intraepithelial lesions or cervical cancer is detected at the baseline. HPV16/18 infections show trends that varied with age, a nonlinear trend among Muslim women. In Hindu women the prevalence is highest at age ≤24 years, which linearly drops with increasing age. Abnormal cytology increases significantly in both religion-groups with increasing age. The data show that these Indian Muslim women are equally susceptible to HPV16/18 infection and for the development of abnormal cytology. There is a paucity in epidemiological data, which justifies the need to screen women of all religions for cervical cancer (that includes oncogenic HPV testing).